POLA KOMUNIKASI MASYARAKAT DALAM MENUMBUHKAN KERUKUNAN DI BARUS (STUDI TERHADAP PENGANUT ISLAM, KRISTEN, DAN PARMALIM) - Khatibah Khatibah; Irwansyah Irwansyah; Hasnun Jauhari Ritonga (Universitas Lambung Mangkurat, 2021)
There are several conditions of concern about Barus, namely that Barus is the Islamic Zero Point of the Archipelago, there is also the oldest church the 7th century, Nommensen also came with his mission, in Barus is also the oldest port of stop by world-class traders, in addition to In this area there is also a local religion developing there, namely Parmalim. Despite the variety, harmony is maintained. With this diversity and harmony, it is important to know how the religious communication patterns in the Barus area are. The data were obtained by conducting interviews with parties, then carrying out focused discussions (FGD), and certain matters through observation and document study, as well as tracing historical sites. In addition to the Barus area, the research areas are also in Barus District, North Barus District, Andam Dewi District and Manduamas District. The three sub-districts were formerly part of the Barus Residency area. The approach taken is scientific integration to integrate communication with the sociology of religion in order to find the theory of harmony communication. The results showed that the communication patterns built from the formation of Islamic-Christian communication patterns through visiting and inviting. Christian-Parmalim communication patterns are formed with culture and education. Parmalim-Islam communication pattern occurs with the pattern of doing together and sharing. However, there are no significant interpersonal communication patterns found, so that the theory of harmony communication is not described in detail as expected.